Modeling and Stable Operation Control Method for Airborne Wind Energy System Considering Longitudinal Disturbance Stability - Bixiong LUO; Junliang HU; Yajun YANG; Zongdong REN; Yadong HE (南方能源建设)
[Objective] This paper aims to explore dynamic modeling methods for airborne wind energy systems (AWEs) and trajectory tracking control methods for stable trajectories of kite trains and between kite trains when subjected to longitudinal disturbances in high-altitude wind fields. [Method] Taking a 25 MW-level kite-based AWEs as an example, this study investigated the mechanical response characteristics of kite arrays and constructed a multi-rigid body dynamic model of the kite-based system. In a simulated environment replicating high-altitude wind fields subjected to longitudinal disturbances, the study employed kite attitude control to design synchronous control laws, enabling trajectory tracking and ensuring operational safety of the kite-based system.[Result] The results demonstrate that adjusting the effective windward area of the kite can mitigate longitudinal disturbances caused by variations in high-altitude wind fields, leading to the convergence of errors between the actual and desired trajectories of the kite-based system. Moreover, based on the synchronous control laws designed, synchronization among multiple kite- based systems has been achieved, thereby ensuring collision-free and safe operation. [Conclusion] Using kite attitude control as a basis, a synchronous control strategy can be designed for the operation of kite-based AWEs, thereby achieving the objective of safe and efficient operation control in dynamic high-altitude wind environments.